Ration between rowing stroke rate and distance per stroke with its effect on boat speed in elite junior double scull - Ilic, N.; Ilic, N. (Knowledge - International Journal, 2022)
Previous research that studied differences in rowing stroke rate and distance per stroke, and their influence on speed of the crew during race, monitored parameters were rarely recorded during the entire distance of 2000m and rarely compared between both genders. Female interest in rowing has grown over the years and the number of crews that can qualify for the Olympics has leveled with male. Development of technology and GPS devices contributed a more detailed analysis of listed parameters, given that we get the same variables measured fourty times at a defined race distance. Before, these variables were recorded only four times, at every 500m. The validity of the measured results was not called into question because of the fact that for all World Rowing Championships organized by FISA (World Rowing), officially timekeepers are "Swiss Timing", leader in this field. The biggest advantage is reflected on parameter the distance per stroke, because now it can be easily, indirectly estimated through the total number of strokes. Research has shown that the parameters stroke rate and distance per stroke are inversely proportional, which is a paradox, because in order to achieve a higher speed of the boat, it is necessary to maintain high values of both parameters. Hence the need to define the influence of the mentioned rowing stroke variables on the average speed of the boat. The research was carried out on the basis of race results from World Championships in rowing for juniors in Varese in 2022. The data from the competition are very significant in terms of results, as new World Best Times were set in four categories. The sample of respondents was represented by 44 crews in double scull for both genders (25 respondents in the JM2x category, 19 respondents in the JW2x category). The results showed that there are no significant differences between men and women when it comes to rowing stroke rate, and small differences when it comes to the distance traveled per stroke. Higher values of the distance per stroke are observed with men, than with women, which is logical due to the fact that they have physiologically greater strength and therefore move the boat more during one single stroke. Stroke rate had a very significant correlation with the speed of the boat for men, but for women it did not significantly affect the speed, while the distance per stroke had a high correlation and a very high degree of significance. The different tact and technique of rowing in women's double sculls, together with the new World Best Time (WBT) set in this discipline, is a potential indicator of the emergence of a new current in rowing, which creates a lot of room for more detailed research on this topic.